Impact of strength training on fractal correlation property of heart rate variability and peripheral muscle strength in COPD - Ricci-Vitor, Ana Laura [UNESP]; Soares Dos Santos, Ana Alice [UNESP]; Fernandes De Godoy, Moacir; Cipulo Ramos, Ercy Mara [UNESP]; Pastre, Carlos Marcelo [UNESP]; Marques Vanderlei, Luiz Carlos [UNESP] (My University, 2014)
Purpose: to evaluate the effect of strength training on fractal properties of heart rate dynamics and heart rate variability (HRV) indices in the time and frequency domains, and peripheral muscle strength in COPD. Methods: an initial and final evaluation of fractal properties of heart rate dynamics, autonomic evaluations (HRV) and strength evaluation (dynamometry) was performed. In addition by the strength training performed by 24 sessions lasted 60 minutes each one and on a frequency of three times a week. The intensity was determined initially with 60% of 1 maximum repetition and was progressively increased in each five sessions until 80%. Results: the training undertaken promoted a short-term increase in the properties of fractal the correlation [0,92 x 1,00, p<0,05], raising their values towards a more chaotic dynamic, in addition to increased peripheral muscle strength [46,85 x 53,12, p<0,05 to shoulder abduction and 91,05 x 102,09, p<0,05 to knee flexion] and autonomic modulation. Conclusions: the exercise program performed was able to restore, at least partially, the fractal nature of heart rate time series in subjects with COPD, as well as improvement in muscle strength and peripheral autonomic modulation.
Keywords: Autonomic nervous system; Chronic obstructive pulmonary disease; Exercise; Fractals; Nonlinear dynamic